Functional outcomes in patients with facial dysostosis and severe upper airway obstruction. Issue 7 (July 2021) - van der Plas, P.P.J.M.; Yang, S.; Streppel, M.; Pullens, B.; Versnel, S.L.; Koudstaal, M.J.; Wolvius, E.B.; Mathijssen, I.M.J.; Joosten, K.F.M.
Abstract: An increased risk of upper airway obstruction (UAO) is seen in up to 95% of patients with facial dysostosis. Secondary to respiratory problems are feeding difficulties and increased nutritional requirements. Little has been described regarding these outcomes in this patient population. Hence, a retrospective cohort study was performed to gather data on functional outcomes. Eighteen patients with facial dysostosis and severe UAO were included. The median follow-up time was 3.42 years. A tracheostomy tube was placed in 13 patients, of whom 10 subsequently underwent mandibular distraction. Three of the five patients without a tracheostomy underwent mandibular distraction as the primary surgical treatment; the remaining two patients were treated conservatively with oxygen supplementation. At presentation, 13 patients had feeding difficulties. Overall malnutrition was present in 16 patients during follow-up. At the end of follow-up, severe UAO was present in 12 patients, feeding difficulties in seven patients, and malnutrition in four patients, while two patients died. In conclusion, patients with facial dysostosis have a high prevalence of severe UAO, feeding difficulties, and malnutrition. Importantly, mandibular distraction has limited success in treating severe UAO in these patients. Close follow-up by a specialized craniofacial team is of paramount importance to manage the long-term consequences.